SISTEM INFORMASI KOORDINASI KELENGKAPAN DEWAN PADA DEWAN PERWAKILAN PERWAKILAN RAKYAT DAERAH PROVINSI KEPULAUAN RIAU - Noviana, Nina (KITA Institut, 2020)
Coordination report complete information system of the council is one of the supporting tools in reporting the council's activities to the Riau Islands Province DPRD. Every matter concerning official organizational activities is always realized in the form of a coordinating report on the completeness of the board. The Office of the Regional Representative Council (DPRD) of the Riau Islands Province also faces obstacles in the coordinating report on the completeness of the board, where the coordinating report on the completeness of the council requires physical evidence and is recorded in a structured manner. This research builds a management information system for coordinating reports on the completeness of the DPRD Kepri council that can be accessed through an internet connection and is built using a web-based computer programming language. This research was conducted in 2016, the research design used was applied research. From the results of the achievement of research conducted that the complete co-ordination information system of the board can be used as an alternative to the management of archiving letter data involving many types and functions of a letter. Ease of access and operations that can be used on various devices is a priority and functionality of an application by using a web-based application. The application of information technology and the demands of work efficiency in agencies requires the ideas and creativity of users at a government agency to innovate in handling performance issues, especially the management and management of letters. It is expected that this application will become the basis for further development in various government agencies to create an e-government application towards good governance.Keywords:Information System, Coordination of Completeness of the Board, DPRD Riau Islands